2015
DOI: 10.1007/s15010-015-0807-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus in the countries of the Middle East and North Africa region: an awareness of an infectious threat to blood safety

Abstract: In the MENA region, the role of HEV as an infectious threat to blood safety is under-investigated. More data are needed to quantify the risk of transmission and to assess clinical outcomes. This requires, at least, surveillance screening of donors and recipients for HEV markers using sensitive and specific serological tests. At the present time, serious consideration should be given to selective screening for certain groups of patients (e.g., immunocompromised, pregnant women and others) who commonly require b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 115 publications
3
30
1
Order By: Relevance
“…A recent review reported that the anti-HEV seroprevalence in the general population in countries of the Middle East and the Northern African-region, where also Morocco is situated, ranges from 2 to 38 % [24]. This is lower than the 44 % weighted prevalence that we found among first generation Moroccans in Amsterdam.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent review reported that the anti-HEV seroprevalence in the general population in countries of the Middle East and the Northern African-region, where also Morocco is situated, ranges from 2 to 38 % [24]. This is lower than the 44 % weighted prevalence that we found among first generation Moroccans in Amsterdam.…”
Section: Discussioncontrasting
confidence: 76%
“…Only two persons were found to have positive IgM for HEV. INFECTION has reported on the growing awareness of HEV not only in special risk populations but also in the area of transfusion services [10].…”
Section: The European Congress Of Clinical Microbiology and Infectioumentioning
confidence: 99%
“…It has been reported that a slow shift in the age of infected subjects from childhood to adulthood has been observed (14). The hepatitis D virus (HDV) appears to be endemic in the ME region (15), and the hepatitis E virus is reported to have a prevalence ranging from 2.0% to 37.5% in countries of the ME and North Africa (16). Furthermore, other types of hepatitis, including non-viral (autoimmune and drug-induced) hepatitis, have been reported in the region of the ME (17,18).…”
Section: Introductionmentioning
confidence: 99%